2003
DOI: 10.1046/j.1365-2265.2003.01792.x
|View full text |Cite
|
Sign up to set email alerts
|

Is ovarian and adrenal venous catheterization and sampling helpful in the investigation of hyperandrogenic women?

Abstract: Our results suggest that ovarian and adrenal venous catheterization and sampling should not be performed routinely in women presenting with symptoms and signs of hyperandrogenism, even if they fail to suppress their elevated androgen levels to a formal 48-h LDDST. All patients presenting with symptoms and signs of hyperandrogenism and elevated androgen levels, and where the suspicion of an androgen-secreting tumour is high, should have adrenal CT and ovarian ultrasound imaging to detect such a tumour. Venous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 39 publications
2
69
0
4
Order By: Relevance
“…polycystic ovarian syndrome, hyperthecosis, Cushing's syndrome, congenital adrenal hyperplasia, and iatrogenesis (see for review (1)). Symptoms of androgen excess are associated with a tumoral pathology in !1% of women of all ages (2)(3)(4)(5). Androgen-producing ovarian tumors include lipoid, Leydig cell, granulosa-theca cell, and Sertoli-stromal cell tumors (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…polycystic ovarian syndrome, hyperthecosis, Cushing's syndrome, congenital adrenal hyperplasia, and iatrogenesis (see for review (1)). Symptoms of androgen excess are associated with a tumoral pathology in !1% of women of all ages (2)(3)(4)(5). Androgen-producing ovarian tumors include lipoid, Leydig cell, granulosa-theca cell, and Sertoli-stromal cell tumors (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that ovarian and adrenal venous catheterization and sampling not be performed routinely in women presenting with symptoms and signs of hyperandrogenism; venous catheterization and sampling should be reserved for patients in whom uncertainty remains [8]. We omitted ovarian vein blood sampling, since ovarian tumor had been diagnosed with transvaginal sonography preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers favor the use of SVCHS, but also point out its low feasibility, the need for expertise and the high failure rate of catheterization as drawbacks. SVCHS is not recommended to be performed routinely for the investigation of hyperandrogenic women but in the presence of a small ovarian tumor when all endocrinologic studies and imaging results fail, it should be kept in mind as a last resort for definitive diagnosis [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although transvaginal ultrasound, computed tomography or magnetic resonance imaging (MRI) might sometimes demonstrate a tumor, a small lesion of less than 2 cm is usually difficult to be detected [4]. Selective venous catheterization and hormonal sampling (SVCHS) of at least four venous vessels (bilateral ovarian-adrenal veins) might help to confirm the presence of an androgen producing tumor either in the ovary or adrenal gland and its laterality [5].…”
Section: Introductionmentioning
confidence: 99%